Rising wages and declining employment: The Brazilian manufacturing sector in the 90s - Marcos Chamon (Institute for Applied Economic Research (ipea), 2015)
The 90s have been quite an eventful decade in Brazilian macroeconomics. There have been recessions, recoveries, hyperinflation, trade liberalization, many failed stabilization attempts, a successful one, exchange-rate overvaluation, just to name a few. Despite all these, since the beginning of this decade there has existed a strong trend for rising wages and declining employment in the manufacturing sector, which is somewhat surprising since historically employment and wages have moved together. The very same period is marked by an astonishing productivity growth in manufacturing that can do much to explain how employment and wages behaved the way they did. This paper explores this productivity issue, making some conjectures as to its origins and how it can shed light into this problem. This paper will also address the issue of substitution of labor by capital, and to which extent it can account for the decline in manufacturing employment. While data availability prevents us from obtaining a good estimate of the substitution between labor and capital, it is still possible to obtain rough measures of the cross-price elasticity of labor and capital. With those estimates and data on relative input price changes it is possible to assess the role of factor substitution in the observed decline in employment.
Keywords: 330